2004
DOI: 10.1007/s00383-004-1223-6
|View full text |Cite
|
Sign up to set email alerts
|

Severe esophageal damage due to button battery ingestion: can it be prevented?

Abstract: Batteries represent less than 2% of foreign bodies ingested by children, but in the last 2 decades, the frequency has continuously increased. Most ingestions have an uneventful course, but those that lodge in the esophagus can lead to serious complications and even death. Medline was used to search the English medical literature, combining "button battery" and "esophageal burn" as keywords. Cases were studied for type, size, and source of the batteries; duration and location of the battery impaction in the eso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
0
9

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(136 citation statements)
references
References 26 publications
1
117
0
9
Order By: Relevance
“…[4][5][6] Once the battery is in the restricted space of the oesophagus and in contact with its endothelium, which creates a circuit, it rapidly starts heating up, causing thermal cell damage. In addition, the casing erodes and leaks metals and hydroxide anions.…”
Section: Pathologymentioning
confidence: 99%
See 3 more Smart Citations
“…[4][5][6] Once the battery is in the restricted space of the oesophagus and in contact with its endothelium, which creates a circuit, it rapidly starts heating up, causing thermal cell damage. In addition, the casing erodes and leaks metals and hydroxide anions.…”
Section: Pathologymentioning
confidence: 99%
“…Oesophageal perforation can occur, [8] and the battery can then go on to erode into surrounding structures. The literature describes a wide range of complications, including aortooesophageal fistula, [9,10] which commonly presents as a herald bleed followed by a fatal upper gastrointestinal bleed, bilateral vocal cord paralysis, [9] tracheo-oesophageal fistula, [11] commonly presenting as aspiration pneumonia, oesophageal necrosis [6] and oesophageal stenosis. [5,6] …”
Section: Pathologymentioning
confidence: 99%
See 2 more Smart Citations
“…Esophageal necrosis, perforation, and death have been reported after button battery ingestion [17,26,28]. Although a large study found that mercury toxicity is rare [29], some batteries contain 5 g of mercuric oxide, which is a lethal dose. Lithium, manganese, and other heavy metals found in batteries do not cause toxicity [30,31].…”
Section: Batteriesmentioning
confidence: 99%